Creativity as a Resource of Adaptation in a Politically and Economically Unstable Environment - Vasylkevych, Yaroslava Z.; Lomak, Olha M.; Zozulia, Iryna M.; Kochereva, Diana V.; Kikinezhdi, Oksana M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The purpose of the study was to identify the specifics of creativity in student age and the peculiarities of socio-psychological adaptation in a politically and economically unstable environment, as well as gender and micro group patterns of the relationship between creativity and adaptability. The methods such as the Guilford-Torrance method, “Desire for creativity” Scale, Kettell test, Methods of Moreno sociometry, Leary’s method, and Dembo-Rubinstein method were used to monitor the variables. The study identified that non-verbal creativity develops in individuals aged 16-17 years. The creative attitude to life develops in the ones aged 17-18. At the age of 18-19, creativity becomes the most integrated into the system of personal characteristics are motivational and personal components of creativity, which form positive connections with the fundamental adaptive personality characteristics, which indicates a greater adaptive resource of creatively oriented individuals. It was also found that boys, compared to girls, were more prone to leadership, more persistent, assertive (E), more emotionally stable (C), calm (O), and also more independent (Q2). Girls were more likely to feel guilty, anxious (O), more sociable, open (A), sensitive, and vulnerable (I). The study found that students with a high level of development of divergent thinking and its components (cognitive factors of creativity) carry out interpersonal communication (as a component of adaptation) most flexibly and effectively making students less prone to depersonalisation and reducing the risk of emotional exhaustion and maladaptation.